Employment Standards Database - York University. Global Labour Research Centre; York University. Department of Politics; Vosko, Leah F. (2025)
The Employment Standards Database is a research database for comparing employment standards, awareness and violations across national/regional context. It brings together a library of relevant sources, unique user-friendly statistical tables, and a thesaurus of concepts – designed to facilitate research on labour market insecurity in a comparative industrialized context. Users can analyze multidimensional tables to explore and compare the contours of precarious employment in Australia, Canada, the United States, and the United Kingdom. –Website description
https://www.sshrc-crsh.gc.ca/results-resultats/prizes-prix/2019/insight_vosko-eng.aspx